Kajian secara teori dan ujikaji terhadap pemampat ram gelangsar berputar - Mat Sarip, Abdul Rahim (2005)
Rotary sliding vane compressor has been a main choice in various applications since 1990’s due to its compact size compared to other compressors with the same capacity. Thus, the mechanical aspects of the compressor need to be studied as the basis for its design. In this thesis, research has been done on mechanical aspect of two rotary sliding vane compressors with a different cylinder shape types and applications which are spherical cylinder rotary sliding vane compressor for air compression and oval cylinder rotary sliding vane compressor with five vanes for automotive air-conditioning system applications. Theoretical studies include the compressor’s mechanical mathematical model for geometry, vane kinematics, vane dynamics, thermodynamic, power and performance. Computer codes for the theoretical simulation have been developed using FORTRAN language. Verification for the first compressor was made using other researcher simulation and testing results. For the second compressor, simulation verification is obtained through experimental results from experimental work that has been done in this research. A test rig for the experimental work is developed using ANSI/ASHRAE Standard 23-1993, ANSI/ASHRAE Standard 41.9-2000 and ISO Standard 917:1989(E). Results that have been presented for both compressors are in the form of comparisons between simulation results and experimental results like volumetric efficiency, cooling capacity, power required and system performance coefficient.